Motivations to Support Marine Conservation Projects in North Tarawa, Kiribati - Turang Teuea; Naohiro Nakamura (Conservation & Society, 2020)
Local communities’ support for resource conservation projects are essential for their success. Nevertheless, in the Pacific Island countries, many community-based conservation (CBC) projects remain ineffective due to the lack of community members’ engagement. To better understand the motivations of local community members to support resource conservation projects; this research looks at the four community-based conservation sites in North Tarawa, Kiribati. We conducted semi-structured interviews and focus group discussions to investigate why community members support (or do not support) CBC. The findings reveal that while local community members are overall aware of the significance of resource conservation, they do not always support or participate in conservation projects. Indeed, the local community members’ motivation to participate in such projects are influenced by various factors, including their status in a household or community, village practices, the quality of community leadership, and their past experiences with similar projects. Our research also finds that community members become unsupportive with conservation projects when their daily livelihood activities are restricted by the projects. This research suggests that project organisers need to understand such factors and be strategic to retain community members’ support for the success of conservation project.